Mimicry diversification in Papilio dardanus via a genomic inversion in the regulatory region of engrailed–invected. Issue 1926 (13th May 2020) - Timmermans, Martijn J. T. N.; Srivathsan, Amrita; Collins, Steve; Meier, Rudolf; Vogler, Alfried P.
Abstract : Polymorphic Batesian mimics exhibit multiple protective morphs that each mimic a different noxious model. Here, we study the genomic transitions leading to the evolution of different mimetic wing patterns in the polymorphic Mocker Swallowtail Papilio dardanus. We generated a draft genome (231 Mb over 30 chromosomes) and re-sequenced individuals of three morphs. Genome-wide single nucleotide polymorphism (SNP) analysis revealed elevated linkage disequilibrium and divergence between morphs in the regulatory region of engrailed, a developmental gene previously implicated in the mimicry switch . The diverged region exhibits a discrete chromosomal inversion (of 40 kb) relative to the ancestral orientation that is associated with the cenea morph, but not with the bottom-recessive hippocoonides morph or with non-mimetic allopatric populations. The functional role of this inversion in the expression of the novel phenotype is currently unknown, but by preventing recombination, it allows the stable inheritance of divergent alleles enabling geographic spread and local coexistence of multiple adaptive morphs.